Prevalencia de Fasciola Hepática en bovinos en la zona rural de Latacunga. - Umatambo Caguano, Joselyn Jazmín (2021)
The general objective of this work was to determine the prevalence of Fasciola hepatica in cattle, which was developed in the rural areas of Latacunga, in order to achieve an effective sanitary management of herds and higher productive yields. The specific objectives were to determine the presence of Fasciola hepatica by the helminth-ovoscopic sedimentation method, to establish the relationship between the prevalence and the factors of origin and sex and also to elaborate the epidemiological map. A total of 100 animals taken at random were used, and the aim was to find out how many animals had this parasite. The samples were obtained directly from the rectum, labeled and taken to the laboratory where the samples were processed using the sedimentation technique, which consists of taking a small sample of feces in a glass, This is repeated as many times as necessary until the water of the sample is clear, then two drops of supernatant are obtained, it is placed in an object holder, a drop of methylene blue is placed, a cover slip is placed and the sample is observed under the microscope. As results, it was found that there is a percentage of 32% of presence of Fasciola hepatica in the rural areas of Latacunga, taking into account the variables measured, it was found that in males the percentage of positives was 15.6%, while 84.4% was found in females. The origin factor showed a higher prevalence in the cantons of Toacaso and Tanicuchi with 10 positive cases respectively. At the end of the study it was concluded that the prevalence of Fasciola hepatica in the rural areas of Latacunga is 32%, which obviously indicates that it is a high percentage.